Let's simplify the expression \((4−2x)(−6x^2+10x+21−2x)\).
First, we simplify the second factor:
\[ -6x^2 + 10x + 21 - 2x = -6x^2 + (10x - 2x) + 21 = -6x^2 + 8x + 21 \]
Now, we rewrite the expression:
\[ (4 - 2x)(-6x^2 + 8x + 21) \]
Next, we can perform the multiplication using the distributive property (also known as the FOIL method for binomials):
\[ = 4(-6x^2) + 4(8x) + 4(21) - 2x(-6x^2) - 2x(8x) - 2x(21) \]
Calculating each term:
- \(4(-6x^2) = -24x^2\)
- \(4(8x) = 32x\)
- \(4(21) = 84\)
- \(-2x(-6x^2) = 12x^3\)
- \(-2x(8x) = -16x^2\)
- \(-2x(21) = -42x\)
Now, combine all these terms together:
\[ 12x^3 + (-24x^2 - 16x^2) + (32x - 42x) + 84 \]
Simplifying the coefficients:
- \(12x^3\)
- \(-24x^2 - 16x^2 = -40x^2\)
- \(32x - 42x = -10x\)
- Constant term remains \(84\)
Putting it all together:
\[ 12x^3 - 40x^2 - 10x + 84 \]
Therefore, the simplified expression for \((4−2x)(−6x^2+10x+21−2x)\) is:
\[ 12x^3 - 40x^2 - 10x + 84 \]
From the provided options, none of them match. Based on our calculations, the result is:
\[ 12x^3 - 40x^2 - 10x + 84 \]
If you'd like further assistance or need help with another problem, feel free to ask!